Association of FTO, LEPR and MTHFR gene polymorphisms with metabolic syndrome in schizophrenia patients receiving antipsychotics - Roffeei, S.N.; Mohamed, Z.; Reynolds, G.P.; Said, M.A.; Hatim, A.; Mohamed, E.H.M.; Aida, S.A.; Zainal, N.Z. (2014)
Aim: The occurrence of metabolic syndrome (MS) in schizophrenia patients receiving long-term antipsychotics (APs) contributes to their high mortality rate. We aimed to determine whether genetic polymorphisms of identified candidate genes are associated with MS in our study population. Materials & methods: We recruited 206 schizophrenia patients receiving AP treatment for at least a year. Cross-sectional measurements of weight, height, blood pressure, waist and hip circumference, and other lipid profiles were recorded. Patient DNA was genotyped for 16 candidate gene polymorphisms. Results: Of these patients, 59.7 were found to have MS while 40.3 did not. All metabolic parameters were significantly different between the two groups. Only three of the 16 polymorphisms studied showed significant association with MS; rs9939609 of the FTO gene confers risk for MS (odds ratio OR: 1.73, 95% CI: 1.07-2.78, p = 0.026), while rs1137101 of the LEPR gene (OR: 0.47, 95% CI: 0.28-0.80, p = 0.005) and rs1801133 of the MTHFR gene (OR: 0.59, 95% CI: 0.35-0.99, p = 0.049) are protective against MS. Conclusion: Polymorphisms of the FTO, LEPR and MTHFR genes may play a role in MS in Malaysian schizophrenia patients receiving long-term treatment with APs.